Diplomatic relations between France and Cameroun - (:unkn) unknown (My University, 2023)
This Ph. D. dissertation aims to study the France-Cameroon and the United States-Cameroon diplomatic relations. More specifically, it intends to show why France-Cameroon relations are "unsteady" and to examine the powerful rise of the United States in the diplomat-ic, economic and cultural areas in Cameroon as from the colonial period to date. To carry out this study, we undertook documentary research on international cooperation, then we inter-viewed some social actors. Located in the heart of the Gulf of Guinea, Cameroon plays a geo-strategic role in sub-Saharan Africa. As a consequence, there has been some latent rivalry in various sectors (diplomatic, economic and cultural) among developed countries, namely France and the United States since the end of the Cold War.However, 63 years after independence, France's "control over Cameroon" tends to de-teriorate considerably. For several decades, the country has been facing multifaceted crises including socio-economic crises, terrorism and the Anglophone crisis in the North-West and the South-West. Thus, the Cameroonian diplomacy seeks credible partners who can contribute to security, development and the recovery of the national economy on the international scene. Today, Cameroon finds itself in a very uncomfortable situation with France and the United States. This delicate situation raises the following question: is the country caught in between hammer and anvil? Let’s recall that this France-Cameroon open-air diplomacy considerably alters relations between the two countries in certain areas (political and economic). This ap-parently leads to the loss of some commercial privileges France has on Cameroon. The other Western powers (e.g. the United States) take advantage of this opportunity to reorient and boost their policy with this Central African country.Since the opening of the first diplomatic representation by the United States in Came-roon in July 1957, the United States-Cameroon cooperation has
Keywords: African Research